Introduction to Math Olympiad problems - Radin, Michael A. (Michael Alexander) (CRC Press, an imprint of Taylor & Francis Group, 2021)
"Introduction to Math Olympiad Problems aims to introduce high school students to all the necessary topics that frequently emerge in international Math Olympiad competitions. In addition to introducing the topics, the book will also provide several repetitive-type guided problems to help develop vital techniques in solving problems correctly and efficiently. The techniques employed in the book will help prepare students for the topics they will typically face in an Olympiad-style event, but also for future college mathematics courses in Discrete Mathematics, Graph Theory, Differential Equations, Number Theory and Abstract Algebra. Features Numerous problems designed to embed good practice in readers, and build underlying reasoning, analysis, and problem-solving skills. Suitable for advanced high school students preparing for Math Olympiad competitions."--Provided by publisher.